Liquid-vapor equilibrium and evaporation rate of Cd-Zn liquid alloy - Zhao W.-C.; Xu B.-Q.; Yang H.-W. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this study, LVE (liquid-vapor equilibrium) data of cadmium-zinc system were determined at a pressure of 7.5 Pa. We compare the use of the Redlich-Kister polynomials with the Wilson equation in fitting activities. The LVE for Cd-Zn system in vacuum distillation was modeled using the two models. The results of the two models are reliable, the Redlich-Kister polynomials are better than the Wilson equation. The LVE phase diagram is reliable for predicting the process of vacuum distillation for Cd-Zn system. The evaporation rates of the elements in Cd-Zn alloy were experimentally measured and calculated by the Langmuir equation. The experimental data on the evaporation of pure metals Cd and Zn are included. The evaporation coefficients of zinc and cadmium under vacuum conditions were calculated. The deviations were discussed. Comparing the calculations with the experimental results, it can be found that the trend is consistent. The activation energies of Cd and Zn in the Cd-Zn alloy under experimental conditions were also calculated.